Roze’ - Sewar Aslan; Shahd Salahat (My University, 2025)
The days when one size fits all are gone. In this era, modern consumers require something more than what was the standard in the previous years – a more personalised approach to their needs. Our project Roze‘, strive to transform the flower and gifting market by providing an innovative application and website that allows customers to create memorable gifts. In addition, Roze‘ creates bonds by allowing people to gift their friends personalized bouquets whatsoever the distance. A few touches on your device’s screen are all it takes to ease the distance and show that you care in any special moment. Essential to the Roze concept is the state-of-the-art AI driven and powered personalization system. With the help of the easy to use customization tool or by simply stating what look, occasion and price are expected, users can easily create their ideal flower bouquets . In addition, the excellent image-processing skills of Roze‘ make all the difference in truly identifying flower types to create truly outstanding arrangements. Apart from personalization, Roze‘ provides a marketplace that connects customers with a network of local florists; users can browse trending designs or place an order. To ensure some kind of competition and, therefore, always offer customers the best offers, Roze‘ allows the florist to bid on a particular order with a guarantee of fairness in value. Roze‘ has a feedback loop in order to improve the platform and user experience over time. Customers can contribute thoughts and feedback, which enhances the AI and provides florists with helpful data. Additionally, Roze‘ simplifies business operations by offering a comprehensive dashboard for managing items, orders, and payments. Roze‘ is a platform that inspires people to express their creativity and create meaningful, one-of-a-kind presents rather than just an app. Roze‘, with its cutting-edge technologies and emphasis on user experience, is ideally positioned to revolutionize the floral and gifting industry and become the go-to option for people searching for unique and memorable gifts. 11